A STATE OWNERSHIP STRATEGY IN INCREASING STATE REVENUE: CASE STUDY AND POLICY ANALYSIS - Shinta Nuriyah Dwi Astutik; Hawiwin Fitriah (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2025)
Fiscal policy in Islamic economics includes various instruments that not only aim to regulate state revenues and expenditures, but also to ensure justice and the economic welfare of society. One of the instruments of fiscal policy in Islam is ghanimah and fa'i , which have an important role in creating a just and sustainable economic structure. This paper aims to examine ghanimah and fa'i as instruments of fiscal policy in Islamic economics, by discussing the three main functions of fiscal policy, namely allocation, distribution, and stabilization. This discussion is conducted through the perspective of the fuqaha, to understand how the implementation of this instrument can play a role in managing state finances. In addition, this paper also raises several issues related to state ownership as state revenue, such as sources of state ownership, how to manage state assets, management of assets that do not have heirs, and assets belonging to apostates. The results of this study are expected to provide a deeper understanding of the management and implementation of fiscal policy in Islamic economics and its impact on the welfare of the people.